Experimental study on the effect of curved tube of premixed hydrogen-air explosion - Siti Zubaidah, Sulaiman; Rafiziana, Md. Kasmani; Azeman, Mustafa (Taylor's University, 2015)
This paper presents the influence of bending and retonation effect on the overpressure and flame propagation on hydrogen-air and methane-air mixtures at ambient condition, ranges between13 to 54 % v/v. The curved pipe consists of 5.1 m long, 0.1m diameter tube, giving a total volume of 0.042 m3 . From the results, it was observed that the highest explosion severity occurred at slightly rich concentration (Ф=1.2) or 36% v/v. giving a maximum overpressure of 8 bar. It was also interesting to note that pressure at the pipe downstream exhibits in a circa of 2 times higher overpressure as compared at the bend. The complex interaction between the flame stretch, fast flame and pressure wave (acoustic wave) effect at the end wall or retonation, would be best described on the phenomenon observed.